Two paradoxes of bounded rationality - Thorstad, D (Michigan Publishing, 2022)
My aim in this paper is to develop a unified solution to three paradoxes of bounded rationality. The first is the regress problem that incorporating cognitive bounds into models of rational decisionmaking generates a regress of higher-order decision problems. The second is the problem of rational irrationality: it sometimes seems rational for bounded agents to act irrationally on the basis of rational deliberation. The third is the rational inevitability of maximization: it seems that behavior must maximize some important quantity such as value or choiceworthiness in order to be rational, contradicting the claim that bounded rationality is a form of satisficing rather than maximization. I review two strategies which have been brought to bear on these problems: the way of weakening which responds by weakening rational norms, and the way of indirection which responds by letting the rationality of behavior be determined by the rationality of the deliberative processes which produced it. Then I propose and defend a third way to confront the paradoxes: the way of level separation.